Pengaruh Substitusi Whip Cream dengan Susu Kedelai terhadap Karakteristik Ganache - Pramono, Bianca Fawwaz; Sugitha, I Made; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPA, 2025)
Ganache is a complementary product in pastry and bakery, made primarily from chocolate and whipped cream. Whipped cream is high in saturated fat and cannot be consumed by everyone, such as vegans and lactose intolerant individuals. Soy milk can be used as a substitute because it has a low fat content and comes from plants. This study aims to determine the effect of substituting whipped cream with soy milk on the characteristics of ganache and to obtain the substitution treatment that produces ganache with the best characteristics. The research was conducted using a Completely Randomized Design with 5 levels of substitution of whipped cream with soy milk, namely; P0 (0%), P1 (25%), P2 (50%), P3 (75%), and P4 (100%) which were repeated 3 times. The parameters tested were water content, fat content, protein content, texture, emulsion stability, and sensory tests including intensity tests and hedonic tests. The results of proximate, texture, and emulsion stability tests were analyzed using analysis of variance, if influential, then the Least Significant Difference test was continued. Sensory assessment was analyzed using Principal Component Analysis. The results showed that soy milk substitution had a significant effect on water content, fat content, protein content, texture, and emulsion stability. Treatment P2 (substitution of whipped cream with 50% soy milk) produced the best soy milk substitution ganache , which had a water content value of 33.81 percent, fat content of 35.16 percent, protein content of 4.11 percent, texture of 16 percent, emulsion stability, color intensity value of 3.96 percent, aroma intensity of 3.4 percent, taste intensity of 3.6 percent, and mouthfeel intensity of 3.43 percent. Hedonic assessments were obtained with an average preference for color, aroma, taste, and overall acceptance. Keywords : ganache, soy milk, whipped cream, chocolate, emulsion